Holistic Family Medicine Approach in Managing Bartholin’s Gland Abscess with Comorbid Type 2 Diabetes Mellitus, Hypertension, and Obesity - Nur Rakhmani, Alidha; Fitri Adinda , Nadiva (Jurnal Ilmu Kedokteran Keluarga, 2026)
Background: Bartholin’s gland abscess is a localized vulvovaginal infection that may be complicated by systemic diseases such as diabetes mellitus, hypertension, and obesity. In family medicine, management requires a holistic and family-oriented approach. Objective: To describe a holistic family medicine approach in managing a patient with Bartholin’s gland abscess and chronic comorbidities. Methods: The family medicine framework was applied, analyzing biological, psychological, social, spiritual, and cultural aspects. Family-focused and community-focused interventions were designed to support comprehensive care. Results: Family involvement, especially from the spouse and children, was crucial to support adherence to therapy, diet, and lifestyle modification. Community interventions, including health promotion at Posbindu PTM and local health campaigns, reinforced prevention strategies. Conclusion: Holistic family medicine care is essential for patients with chronic comorbidities and recurrent infections. This approach integrates medical therapy, family support, and community engagement to improve outcomes.